Rasch Validation of Arabic Scale of Mental Health (ASMH) in Indonesian Version to Measure Adolescent Mental Health - Hartanto, Dody; Fauziah, Mufied; Rizal, Yenni; Azhari, Imam; Matahari, Ratu; Fauzan, Parhan; Hanum, Nuri Cholidah; Herdiansyah, Diki (Jurnal Kajian Bimbingan dan Konseling, 2024)
Mental health is a crucial aspect for adolescents, as those with poor mental health may experience conditions ranging from depression and anxiety disorders to suicidal tendencies. Identifying mental health issues is essential, necessitating an instrument to assess adolescent mental health. This study aims to adapt the Arabic Scale of Mental Health (ASMH) into Indonesian and evaluate its validity using the Rasch model. The adaptation process followed the Procedures and Guidelines for Translating Counselling Assessment as outlined by Lenz, Gómez Soler, Dell'Aquilla, and Uribe. The translated instrument was administered to 685 high school and vocational school students from Yogyakarta. The instrument was then analyzed using the Rasch model to determine its suitability for use. Results indicate that the adapted instrument is deemed appropriate for use based on statistical analysis using the Rasch model.